Searching for high ZnPP-forming edible bacteria to improve the color of fermented meat products without nitrite/nitrate. (July 2020) - Asaduzzaman, Md; Ohya, Momo; Kumura, Haruto; Hayakawa, Toru; Wakamatsu, Jun-ichi
Abstract: In order to improve the color of meat products by producing zinc protoporphyrin IX (ZnPP) in meat, we searched for edible bacteria with high ZnPP-forming ability. Eleven bacteria used in different animal products and 126 bacteria isolated from environmental and probiotic sources were assessed for their ability to form ZnPP. Many bacteria from both sources showed a high ZnPP-forming ability. Only three edible bacteria were identified from the 44 high ZnPP-forming isolates with 16S rRNA gene sequencing. High ZnPP-forming bacteria from both sources were inoculated in aseptic salt-added minced meat, and their ZnPP-forming abilities were evaluated. Lactococcus lactis, Leuconostoc mesenteroides, and Enterococcus faecium from environmental isolates produced a brighter red color, higher ZnPP autofluorescence and fluorescence intensity in salt-added minced meat than control. Furthermore, after heating, the color and ZnPP autofluorescence of the inoculated minced meat persisted to a degree. Therefore, it is possible to improve the color of meat products without nitrite/nitrate by using these promising ZnPP-forming edible bacteria. Highlights: High ZnPP-forming edible bacteria were found and identified. Selected bacteria produced a large amount of ZnPP in meat models. ZnPP formed by the promising bacteria was heat-stable in meat. ZnPP formed by the promising bacteria could improve the color of meat products.